2004
DOI: 10.1021/jm031031i
|View full text |Cite
|
Sign up to set email alerts
|

First Reported Nonpeptide AT1Receptor Agonist (L-162,313) Acts as an AT2Receptor Agonist in Vivo

Abstract: In this investigation, it is demonstrated that the first nonpeptide AT(1) receptor agonist L-162,313 (1), disclosed in 1994, also acts as an agonist at the AT(2) receptor. In anesthetized rats, administration of compound 1 intravenously or locally in the duodenum increased duodenal mucosal alkaline secretion, effects that were sensitive to the selective AT(2) receptor antagonist PD-123,319. The data strongly suggest that 1 is an AT(2) receptor agonist in vivo. To the best of our knowledge, this substance is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 24 publications
1
37
0
1
Order By: Relevance
“…In this context, Wan et al (2004b) have recently described the first non-peptide, selective AT2 receptor agonist, Compound 21 (N-butyloxycarbonyl-3-(4-imidazol-1-ylmethylph enyl)-5-isobutylthiophene-2-sulphonamide). Compound 21 was derived from a medicinal chemistry programme aimed at transforming the drug-like but non-selective AT1 and AT2 receptor agonist L-162313 (Wan et al, 2004a) into a selective AT2 receptor agonist. Compound 21 exhibits a Ki value of 0.4 nM for the AT2 receptor and a Ki > 10 mM for the AT1 receptor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, Wan et al (2004b) have recently described the first non-peptide, selective AT2 receptor agonist, Compound 21 (N-butyloxycarbonyl-3-(4-imidazol-1-ylmethylph enyl)-5-isobutylthiophene-2-sulphonamide). Compound 21 was derived from a medicinal chemistry programme aimed at transforming the drug-like but non-selective AT1 and AT2 receptor agonist L-162313 (Wan et al, 2004a) into a selective AT2 receptor agonist. Compound 21 exhibits a Ki value of 0.4 nM for the AT2 receptor and a Ki > 10 mM for the AT1 receptor.…”
Section: Introductionmentioning
confidence: 99%
“…Compound 21 was derived from a medicinal chemistry programme aimed at transforming the drug-like but non-selective AT1 and AT2 receptor agonist L-162313 (Wan et al, 2004a) into a selective AT2 receptor agonist. Compound 21 exhibits a Ki value of 0.4 nM for the AT2 receptor and a Ki > 10 mM for the AT1 receptor.…”
Section: Introductionmentioning
confidence: 99%
“…This process gave the corresponding alcohols 14-18 in good yields. The alcohols (14)(15)(16)(17)(18) were then subsequently oxidized with pyridiniumchlorochromate in dichloromethane to give the (4-bromophenyl)-heterocyclic-methanones (19)(20)(21)(22)(23) in high yields.…”
Section: Chemistrymentioning
confidence: 99%
“…1). [17][18][19] The unsubstituted imidazole provided a good moiety to obtain high affinity, AT 1 /AT 2 selectivity as well as agonism. We have also shown that 0968 the unsubstituted imidazole could be combined with substituents other than iso-butyl in the 5-postion of the thiophene.…”
Section: Introductionmentioning
confidence: 99%
“…46 In addition, AT2R agonists that enhance the antiproliferative and apoptotic effect of AT2R expression are emerging. 47,48 These therapeutic options remain experimental or at the laboratory levels, yet these novel directions represent a new paradigm to intervene in the progression of renal failure in IgAN by reducing tubulointerstital injury.…”
Section: Future Therapeutic Targets For Iganmentioning
confidence: 99%